High symmetry nano-photonic quasi-crystals providing novel light management in silicon solar cells. (June 2021) - Mercier, Thomas M.; Rahman, Tasmiat; Krishnan, Chirenjeevi; Khorani, Edris; Shaw, Peter J.; Pollard, Michael E.; Boden, Stuart A.; Lagoudakis, Pavlos G.; Charlton, Martin D.B.
Abstract: Reduction of surface reflection loss is crucial for high efficiency next generation Si solar cells. Surface texturing provides a viable method to reduce loss over the full solar bandwidth. Previous studies have concentrated on simple moth-eye silicon pillar arrays protruding from the surface. Using FDTD simulation methods, we undertake a systematic investigation into performance benefits provided by complex semi-random photonic quasi-crystal surface patterning methodologies whereby arrays of air holes are etched deep into the solar cell surface. In contrast to other studies we carefully investigate the effect of lattice symmetry, systematically comparing performance of simple 6-fold symmetric triangular photonic crystal patterning to 12 fold symmetry photonic quasicrystal patterning and infinitely symmetric 2D Fibonacci patterning. We optimize key geometric parameters such as lattice pitch, hole size and etch depth to maximize optical performance for each lattice type. 12 fold photonic quasi crystal lattice is found to provide best overall anti-reflectance performance providing a solar-corrected average reflectance of 8.3% for a hole depth of 1.5 µm and 300 nm diameter, in comparison to 36.4% for a bare silicon solar cell surface. Practical feasibility of the optimal designs is demonstrated by fabrication of physical prototypes consisting of arrays of nm scale air-holes etched into the surface of a silicon slab fabricated Using e-beam lithography and ICP/RIE etching. FDTD Simulation methodology is validated by convergence studies as well as comparison to optical measurements on these fabricated devices. Furthermore, in contrast to previous studies we provide an in depth analysis of the physical mechanisms responsible for reduction in surface reflection, determining the parameter space where conventional Gaussian optical processes such as effective refractive index, refraction and Fresnel reflection dominate, vs parameter space where sub wavelength photonic crystal scattering effects play the main role. We finish up with an analysis of electrical performance for the optimal designs to further validate real world performance. Taking electrical performance into account we determine that infinite-symmetry 2D Fibonacci patterning far outperforms lower symmetry 12 fold and triangular arrangement. We believe that this is the first in depth investigation into 2D Fibonacci patterning in silicon solar cells. Graphical Abstract: ga1 Highlights: Photonic Quasi Crystals go beyond simple effective medium effects. Semi-random structures can be accurately simulated in FDTD using large domain sizes. Triangular, 12 fold and Fibonacci lattices interact markedly different with light. The physics of diffractive structures in Silicon is analyzed. Fabrication of nanostructures is demonstrated via E-Beam lithography.